Evaluation of In Vitro Fertilization Outcomes in Women with Hypogonadotropic Hypogonadism - Oya Aldemir; Yaprak Ustun; Runa Özelçi; Berna Dilbaz; Serdar Dilbaz; Kübra Dilbaz (Düzce Tıp Fakültesi Dergisi, 2023)
Aim: Hypogonadotropic hypogonadism (HH) is a rare clinical condition resulting from gonadal insufficiency due to low pituitary gonadotropin levels. Since ovulation occurs rarely in these patients, the probability of spontaneous pregnancy is very low. The study aimed to evaluate the in vitro fertilization (IVF) treatment outcomes in patients with HH and to compare these results with that of patients with unexplained infertility (UI) who underwent IVF treatment. Material and Methods: In this study, 36 cycles of 28 HH patients who underwent IVF treatment and 72 cycles of 68 patients who underwent IVF treatment for UI were included. Demographic data, ovarian hyperstimulation and cycle outcomes, clinical pregnancy rates, and predictive factors for clinical pregnancy were evaluated retrospectively, and the two groups were compared. Results: In the HH group, clinical pregnancy, and live birth rates per cycle after IVF were significantly higher compared with the UI group (n=16, 44.4% vs. n=17, 23.6%, p=0.027; and n=14, 38.9% vs. n=14, 19.4%; p=0.030, respectively). Although the number of antral follicles (p=0.001) and retrieved oocytes (p=0.042) were significantly higher in the UI group, the number of mature oocytes and grade I-II embryos were similar in the HH and UI groups. The total gonadotropin dose used and duration of stimulation in the HH group were significantly higher than in the UI group (both p=0.001). Conclusion: HH patients responded well to IVF treatment and had better IVF outcomes compared to women who underwent IVF for UI. No prognostic factor that affected pregnancy success in HH patients was detected.